Por uma sociologia das emergências: perspectivas emancipatórias nos territórios de produção das ausências amazônicas - Lacerda, Luiz Felipe Barboza (Universidade do Vale do Rio dos Sinos, 2016)
This thesis starts from some questions to make a social-historical analysis of Amazon. How the Brazilian state, over time, has established relations with the native peoples of the Amazon Forest? What are the implications of interventions carried out by the State and other civil actors in these territories? How and with what strategies indigenous peoples and river-dwelling communities deal with the advancement of the exploitative capitalist practices over their cultures and territories? We assert that the process called "progress" sees the forest as an obstacle to its notion of development, establishing with it a utilitarian relationship, based on commercial nexus, generating social invisibility to people that lives in it. For such populations, emancipating themselves means to seek autonomy and sovereignty on basic and reproductive aspects of everyday life, precisely in what public policies did not managed to build in the Amazon territories. The thesis aims to discuss what is needed for such populations to take the lead of the intervention processes in their territories, in order to direct investments to what they believe foster real emancipation and development, in their own terms. The hypothesis we worked with is that the principles of cooperation, solidarity and self-management are effective tools in building stronger communities, able to take these processes forward in pursuit of their goals of Good Living. We noticed that it’s not enough to think of new forms of intervention, but it is also imperative to innovate in ways we evaluate these interventional practices. To demonstrate these hypotheses, as well as its consequences, we undertook intense and thorough immersion in twenty-two indigenous and river-dwelling communities in the Alto Solimões, Amazon territory of production of absences. For this immersion, we used the Samaúma’s, the Onça’s and the Tucandeira Ant’s looks, metaphors drawn from the forest reality, in order to better understand it.
Keywords: Amazônia; Povos tradicionais; Sociologia das ausências e emergências políticas públicas; Emancipação social; Bem viver; Social policy; Social emancipation; Good living; Indigenous; River-dwelling communities; Sociology of absences and emergencies; ACCNPQ::Ciências Humanas::Sociologia